2018
DOI: 10.1371/journal.pone.0198312
|View full text |Cite
|
Sign up to set email alerts
|

Using event-related fMRI to examine sustained attention processes and effects of APOE ε4 in young adults

Abstract: In this study we investigated effects of the APOE ε4 allele (which confers an enhanced risk of poorer cognitive ageing, and Alzheimer’s Disease) on sustained attention (vigilance) performance in young adults using the Rapid Visual Information Processing (RVIP) task and event-related fMRI. Previous fMRI work with this task has used block designs: this study is the first to image an extended (6-minute) RVIP task. Participants were 26 carriers of the APOE ε4 allele, and 26 non carriers (aged 18–28). Pupil diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Furthermore, both genotype groups showed a decline in target detection (after accounting for response bias) from conditions of low to high executive demand, although robust analyses suggest this result should be interpreted with caution. Notably, an imaging study using the same sustained attention paradigm as the current study also reported no genotype behavioural differences in correct hits or target detection in young adults but instead saw different patterns of activation and cognitive effort indexed through pupillometry, suggestive of different cognitive strategies across genotypes [67].…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, both genotype groups showed a decline in target detection (after accounting for response bias) from conditions of low to high executive demand, although robust analyses suggest this result should be interpreted with caution. Notably, an imaging study using the same sustained attention paradigm as the current study also reported no genotype behavioural differences in correct hits or target detection in young adults but instead saw different patterns of activation and cognitive effort indexed through pupillometry, suggestive of different cognitive strategies across genotypes [67].…”
Section: Discussionsupporting
confidence: 54%
“…On the other hand, imaging studies of ADHD also confirmed that DAN and VAN were involved in inattention, while SMN and DMN were involved in hyperactivity 35 . However, only a few studies have explored genetic effects on these brain regions when performing attention tasks 9,36,37 . We thus expected that genes associated with sustained attention might also be associated with functional connectivity of these networks.…”
Section: Introductionmentioning
confidence: 94%
“…35 However, only a few studies have explored genetic effects on these brain regions when performing attention tasks. 9,36,37 We thus expected that genes associated with sustained attention might also be associated with functional connectivity of these networks.…”
Section: Introductionmentioning
confidence: 99%
“…fMRI. The fMRI acquisition and preprocessing protocol has been described previously 67 : fMRI datasets were acquired using a T2* -weighted 2D-EPI sequence. To minimise signal artefacts originating from the sinuses, axial slices were tilted 30° from inter-commissural plane.…”
Section: Volumetric Analysesmentioning
confidence: 99%